Exploring the pathway: clinical utility and open challenges of targeting BRAF alterations in biliary tract cancers and gastrointestinal malignancies - L. Weiss; D. Zhang; W.G. Kunz; S. Boeck; G. Curigliano; V. Subbiah; F. Lordick; T. Brummer; C.B. Westphalen; L. Boscolo Bielo (ESMO Gastrointestinal Oncology)
The BRAF proto-oncogene plays a key role in oncogenesis, promoting growth and survival through various genetic alterations. Most mutations involve the substitution of valine at amino acid position 600 (V600), resulting in a constitutively active protein, known as class I alterations. The most common class I mutation encodes for the BRAFV600E oncoprotein. Therapeutic targeting of BRAFV600E has led to the approval of dabrafenib plus trametinib for solid tumours [excluding colorectal cancer (CRC)] refractory to standard therapies. In gastrointestinal cancers, dabrafenib and trametinib have shown remarkable results in biliary tract cancers (BTC), establishing this combination as a viable second-line option for BRAFV600E-mutant BTC. In CRC, intrinsic epidermal growth factor receptor (EGFR) activation circumvents BRAF inhibition, necessitating the concurrent use of EGFR inhibitors, whose treatment strategy led to the approval of encorafenib plus cetuximab for BRAFV600E CRC.Despite these advances, resistance to BRAF inhibitors is almost universal, often due to extracellular signal-regulated kinase (ERK)-mediated up-regulation of RAF dimers that is able to overcome the inhibition of BRAF monomers. This resistance mechanism has spurred the development of novel RAF inhibitors able to prevent or to inhibit RAF dimers. Additionally, several treatment strategies are currently being investigated, including multi-step vertical mitogen-activated protein kinase (MAPK) inhibition and targeting parallel signalling pathways capable of bypassing MAPK oncogenic inhibition. While noteworthy results have been achieved with BRAFV600E inhibition, further research is needed to optimize BRAF-targeted therapies and address resistance mechanisms. Continued research and innovation are crucial to improving patient outcomes and addressing the complexities of BRAF mutations in human cancers.